2014
DOI: 10.1177/0148558x14549460
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Culture on the Quality of Internal Audit

Abstract: This study draws on Hofstede’s theoretical framework to examine the impact of different dimensions of culture on the quality of internal audit (QIA) in Saudi Arabia. A sample of chief internal auditors from 67 listed companies has been used to examine the direct effect of the cultural dimensions of power distance, uncertainty avoidance, and individualism on the QIA. Evidence was found that organizations, in which power distance and uncertainty avoidance are high, are characterized by lower QIA. The results als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 42 publications
(70 reference statements)
3
33
0
2
Order By: Relevance
“…Others, such as China and Malaysia, do require the establishment of an IAF for all listed companies, but they have the right to choose in-house or outsourced arrangements (Abdullah et al, 2018;Johl et al, 2013;Leung & Cooper, 2009;Mat Zain et al, 2015). The absence or existence of such a requirement may explain the variation in IAF quality in these countries; for example, low quality in Egypt, Saudi Arabia, and Jordan (Alzeban, 2015;Ebaid, 2011) and relatively good quality in China and Malaysia (Johl et al, 2013;Leung & Cooper, 2009;Mat Zain et al, 2015).…”
Section: Institutional Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Others, such as China and Malaysia, do require the establishment of an IAF for all listed companies, but they have the right to choose in-house or outsourced arrangements (Abdullah et al, 2018;Johl et al, 2013;Leung & Cooper, 2009;Mat Zain et al, 2015). The absence or existence of such a requirement may explain the variation in IAF quality in these countries; for example, low quality in Egypt, Saudi Arabia, and Jordan (Alzeban, 2015;Ebaid, 2011) and relatively good quality in China and Malaysia (Johl et al, 2013;Leung & Cooper, 2009;Mat Zain et al, 2015).…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…Sarens and Abdolmohammadi () reported that emerging countries prefer to apply US IAF best practices than those of other developed countries. Accordingly, empirical research has emerged to cover some aspects of IAF in, for example, Malaysia (e.g., Abdullah, Ismail, & Smith, ; Johl et al, ; Mat Zain, Zaman, & Mohamed, ), China and Taiwan (Leung & Cooper, ), Egypt (e.g., Ebaid, ), Jordan (e.g., Al‐Sukker, Ross, Abdel‐Qader, & Al‐Akra, ), and Saudi Arabia (e.g., Alzeban, ; Alzeban & Gwilliam, ). However, although outsourcing IAF is the predominant practice in these countries, the evidence from this literature is based on the traditional form of IAF; that is, in‐house.…”
Section: Introductionmentioning
confidence: 99%
“…These studies often report significant variations in practice with respect to the cultural context (Abdolmohammadi & Sarens, 2011;Hughes, Sander, Higgs, & Cullinan, 2009). The empirical work in [S35] examines the influence of three cultural dimensions of the Hofstede's framework, namely power distance, uncertainty avoidance, and individualism, on the quality of internal audits (Alzeban, 2015). Power distance relates to the extent to which the less powerful members of institutions expect and accept that power is distributed unequally (Hofstede et al, 2010).…”
Section: Iaef20 Cultural Dimensionsmentioning
confidence: 99%
“…Whilst frowned upon in Western societies, in many other societies characterized by collectivism rather than individualism, such behavior is expected and loyalty to the extended family is indeed encouraged. That said, as highlighted by several scholars (see for example, Alzeban, 2015;Alzeban & Gwilliam, 2014;Haniffa & Hudaib, 2007), these tribal and friendship relations are powerful and have the strong potential to interfere with the effective monitoring of audit practice. In this matter, Al-Twaijry, Brierley, and Gwilliam (2002) offer concrete evidence of the damaging effect of this phenomenon, highlighting that in Saudi Arabia the intrinsic emphasis on personal connections, and the nature of society and economic enterprise which are characterised by hierarchy and power distance, cause problems for auditors in the fulfilment of their responsibilities since interventions are often made which detract from honest financial reporting.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%